2009
DOI: 10.1007/s10608-009-9275-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates and Treatment Response of the Yale-Brown Obsessive Compulsive Scale Auxiliary Items

Abstract: The current study examined clinical correlates and treatment response as they relate to auxiliary clinical characteristics (i.e., insight; avoidance; indecisiveness; sense of responsibility; pervasive slowness; pathological doubt; duration of obsession-free and compulsion-free intervals) in 172 adults with OCD. A trained evaluator administered the Yale-Brown Obsessive Compulsive Scale and the Anxiety Disorders Interview Schedule for DSM-IV. As well, patients completed the Obsessive Compulsive Inventory-Revised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The second used logistic regression to predict posttreatment wellness (a state characterized by remission of OCD symptoms as indicated by YBOCS ≤ 12). Both models controlled for baseline YBOCS severity because the YBOCS avoidance item is positively associated with overall severity (Reid et al, 2011). To test the specificity of the avoidance–outcome relationship to EX/RP we reran these analyses in the risperidone and placebo groups separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second used logistic regression to predict posttreatment wellness (a state characterized by remission of OCD symptoms as indicated by YBOCS ≤ 12). Both models controlled for baseline YBOCS severity because the YBOCS avoidance item is positively associated with overall severity (Reid et al, 2011). To test the specificity of the avoidance–outcome relationship to EX/RP we reran these analyses in the risperidone and placebo groups separately.…”
Section: Methodsmentioning
confidence: 99%
“…However, the original YBOCS does include an assessment of avoidance behavior among its auxiliary items (which are often overlooked in research; Reid, Storch, & Murphy, 2011). For this avoidance assessment, raters ask patients to rate the extent to which they have been avoiding places, situations, or people because of obsessional thoughts or the need to perform compulsions.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that the obsession-free interval item allowed for improved assessment of the time burden imposed by obsessions and therefore have included it in the Y-BOCS–II. Empirical evidence for this includes moderate correlations between this item and functional impairment (Reid, Storch, & Murphy, 2009).…”
Section: Eliminating the “Resistance To Obsessions” Itemmentioning
confidence: 99%
“… 19 Disability was correlated with insight with regards to OCD, 28 as was the degree of avoidance and pathological doubting. 29 Occupational disability was also associated with poorer social functioning. 30 The Social Adjustment Scale (SAS)-non family score (excludes marital and family functioning score) was significantly associated with hostility expressed by patient's relatives.…”
Section: Resultsmentioning
confidence: 99%